Evaluasi dan Perbaikan Antarmuka Aplikasi Web Daily Plan LPMI Al-Izzah Kota Batu Menggunakan Pendekatan Human Centered Design - Fahmi Nur Fachrurozi; Satrio Hadi Wijoyo; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
LPMI Al-Izzah Batu City is an educational institution that was established on July 17, 2006 by implementing Islamic basic values that ​​integrated with technology and science with the aim that students are able to maintain Islamic sharia. In addition, LPMI Al-Izzah of Batu city also has a web application that can be used by employees in planning daily activities called the Daily Plan. Based on the analysis and testing of the initial design, the results obtained on the aspect of effectiveness of 71.3%, 34.25 seconds efficiency aspects, and aspects of user satisfaction by 41.66. Then the researchers then did the design of improving the interface appearance by applying the Human Centered Design approach, Usability testing method and System Usability Scale. From the evaluation results of the appearance improvement design that has been done, researcher get a percentage of 100% in the aspect of effectiveness, 19.38 seconds in the aspect of efficiency, and 87.83 in the aspect of user satisfaction. From this research, it can be concluded that the Human Centered Design approach is able to produce a product or system that is able to help users and stakeholders achieve their goals.